(untitled) (Editora Impacto Científico, 2025)
The chapter analyzes the activities of the Euclides da Cunha Cultural Center (CCEC), founded in 1947 in Ponta Grossa, Paraná, as a space for the dissemination of scientific, cultural, and educational ideas inspired by a modernizing and Euclidean ideal. The central theme is the articulation between science, culture, and education as instruments for the moral and intellectual formation of society, particularly of the popular classes, through communication media and everyday instructional practices. The objectives are to understand how the CCEC used the newspaper Tapejara, the Rádio Clube Ponta-Grossense, and events such as the Euclidean Week and the Euclidean Intellectual Marathon to promote scientific knowledge, foster reading, and stimulate interest in culture and education. These initiatives sought to consolidate urban ideals of modernity and progress, linking scientific knowledge to the construction of national identity and to the moral enhancement of citizenship. The study is based on theoretical frameworks from the history of science and education, especially Pierre Bourdieu (intellectual field and symbolic power), Sílvia Figueirôa (science as part of culture), Jean-François Sirinelli (journals and intellectual sociability), and Carlos Vieira (education and modernity). The analysis shows that the Euclidean intellectuals of Ponta Grossa understood education not only as formal instruction but as a broader social and cultural process aimed at enlightening the masses, connecting science, morality, and patriotism to their civilizing Project. DOI: https://doi.org/10.56238/edimpacto2025.090-041